Semiquantitative assessment of osteoblastic, osteolytic, and mixed lytic-sclerotic bone lesions on fluorodeoxyglucose positron emission tomography/computed tomography and bone scintigraphy - Gurkan, Guray; Sarikaya, Ismet; Sarikaya, Ali (World Journal of Nuclear Medicine, 2019)
Bone scintigraphy is widely used to detect bone metastases, particularly osteoblastic ones, and F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) scan is useful in detecting lytic bone metastases. In routine studies, images are assessed visually. In this retrospective study, we aimed to assess the osteoblastic, osteolytic, and mixed lytic-sclerotic bone lesions semiquantitatively by measuring maximum standardized uptake value (SUVmax) on FDG PET/computed tomography (CT), maximum lesion to normal bone count ratio (ROImax) on bone scintigraphy, and Hounsfield unit (HU) on CT. Bone scintigraphy and FDG PET/CT images of 33 patients with various solid tumors were evaluated. Osteoblastic, osteolytic, and mixed lesions were identified on CT and SUVmax, ROImax, and HU values of these lesions were measured. Statistical analysis was performed to determine if there is a difference in SUVmax, ROImax, and HU values of osteoblastic, osteolytic, and mixed lesions and any correlation between these values. Patients had various solid tumors, mainly lung, breast, and prostate cancers. There were 145 bone lesions (22.8% osteoblastic, 53.1% osteolytic, and 24.1% mixed) on CT. Osteoblastic lesions had a significantly higher value of CT HU as compared to osteolytic and mixed lesions (P < 0.01). There was no significant difference in mean ROImaxand mean SUVmaxvalues of osteolytic and osteoblastic bone lesions. There was no correlation between SUVmaxand ROImax, SUVmaxand HU, and ROImaxand HU values in osteolytic, osteoblastic, and mixed lesions (P > 0.05). Not finding a significant difference in SUVmaxand ROImaxvalues of osteoblastic, osteolytic, and mixed lesions and also lack of correlation between SUVmax, ROImax, and HU values could be due to treatment status of the bone lesions, size of the lesion, nonmetastatic lesions, erroneous measurement of SUVmaxand ROImax, or varying metabolism in bone metastases originating from various malignancies.
Keywords: Bone scintigraphy; fluorodeoxyglucose positron emission tomography/computed tomography; osteoblastic; osteolytic; semiquantitative